DECREASE IN LABOR INPUT OF PRODUCTION DUE TO RATIONAL USE OF A MANPOWER - E. V. Korneevets; A. V. Burchak (Литьë и металлургия, 2017)
The indicator of labor input is considered. Connection of labor input and labor productivity is given. Major factors of decrease in labor input are formulated. Necessity of continuous decrease in labor input is proved. Options of organizational – technical actions to reduce labor input on an example the steel-wire shops of OJSC «BSW» – Management Company of Holding «BMC» are offered.